The shoulder abductor strength is a novel predictor of tracheostomy in patients with traumatic cervical spinal cord injury - Yunbo Jian; Zhiping Mu; Dawei Sun; Dan Zhang; Chunmei Luo; Zhengfeng Zhang (BMC Musculoskeletal Disorders, 2022)
Abstract Background Early prediction of tracheostomy in traumatic cervical spinal cord injury (TCSCI) patients is often difficult. This study aims to clarify the association between shoulder abductor strength (SAS) and tracheostomy in patients with TCSCI. Methods We retrospectively analyzed 513 TCSCI patients who were treated in our hospital. All patients were divided into a tracheostomy group and a non-tracheostomy group. The SAS was assessed using the Medical Research Council (MRC) Scale for Muscle Strength grading. Potential predictors were assessed for their association with tracheostomy in patients. A nomogram was developed based on multivariable logistic regression analysis (MLRA) to visualize the predictive ability of the SAS. Validation of the nomogram was performed to judge whether the nomogram was reliable for visual analysis of the SAS. Receiver operating characteristics curve, specificity, and sensitivity were also performed to assess the predictive ability of the SAS. Results The proportion of patients with the SAS grade 0–2 was significantly higher in the tracheostomy group than in the non-tracheostomy group (88.1% vs. 54.8%, p = 0.001). The SAS grade 0–2 was identified as a significant predictor of the tracheostomy (OR: 4.505; 95% CI: 2.080–9.758; p = 0.001). Points corresponding to both the SAS grade 0–2 and the neurological level of injury at C2-C4 were between 60 and 70 in the nomogram. The area under the curve for the SAS grade 0–2 was 0.692. The sensitivity of SAS grade 0–2 was 0.239. The specificity of SAS grade 0–2 was 0.951. Conclusions SAS is a novel predictor of tracheostomy in patients after TCSCI. The SAS grade 0–2 had a good predictive ability of tracheostomy.